Rock mass under static loadings - Yi, Zhang. (2009)
Rock engineering has been researched by people for many years. Since it is met commonly in the real engineering works, it is necessary to have a good understanding of rock behaviors in certain loading conditions. Since rock is a kind of heterogeneous materials, it may behaves quite differently even in the same sort of rock. The pure natural rock consist various joints and microcracks, and each joint and crack does have different size, strength and position. This requires the study to have a reliable modeling for the analysis. By doing a reliable model, DDA has been introduced to this study. DDA is a discrete element method with a lot of mechanical functions. It can be used to demonstrate the mechanical behaviors of rock materials under different loading conditions. The aim of this project is to understand the fracture behaviors of rock with different joint property and static loading using DDA. The fracture pattern of the rock mass with different joints will be examined in this report. By linking with the classical fracture theories, the results of the rock mass fractures show a good relationship with the effects of joint property and load pattern. In all, this report will show the simulation process to study the rock mass fracture mechanism by using DDA and discuss the effect of various factors that can affect the result in the numerical method.